2021
DOI: 10.2174/1871530320999201126202706
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Rs780094 and Rs1260326 Polymorphisms in GCKR Gene to Non-alcoholic Fatty Liver Disease: A Meta-Analysis Involving 26,552 Participants

Abstract: Background:: Many published studies attempted to elucidate the implication of glucokinase regulator gene (GCKR) polymorphisms in the susceptibility to nonalcoholic fatty liver disease (NAFLD), but the results among them were still with controversy. Objective:: This meta-analysis aims to precisely assess the relationship between the GCKR polymorphisms and the risk of NAFLD. Methods:: Systematic computerized searches in six databases were performed and updated to April 6, 2020. Meta-analyses were conducted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Five SNPs (rs429358, rs3747207, rs9479542, rs10401969 and rs17321515) were associated with NAFLD at p < 5 × 10 −8 in our primary UKBB GWAS. One SNP, rs1260326, related to NAFLD in a previously published study [ 34 ], and with a high LD with rs780094 (r 2 = 0.91) in Speliotes’ study [ 24 ], had an effect estimate in the same direction but with a p = 1.30 × 10 −7 in our study. Although, two SNPs (rs429358 and rs3747207) associated with NAFLD were missing in the SUNLIGHT consortium, we were able to identify only one SNP that could be used as a proxy (rs738408, p = 9 × 10 −42 ) for the SNP (rs3747207) based upon high LD (r 2 = 0.98).…”
Section: Methodssupporting
confidence: 75%
“…Five SNPs (rs429358, rs3747207, rs9479542, rs10401969 and rs17321515) were associated with NAFLD at p < 5 × 10 −8 in our primary UKBB GWAS. One SNP, rs1260326, related to NAFLD in a previously published study [ 34 ], and with a high LD with rs780094 (r 2 = 0.91) in Speliotes’ study [ 24 ], had an effect estimate in the same direction but with a p = 1.30 × 10 −7 in our study. Although, two SNPs (rs429358 and rs3747207) associated with NAFLD were missing in the SUNLIGHT consortium, we were able to identify only one SNP that could be used as a proxy (rs738408, p = 9 × 10 −42 ) for the SNP (rs3747207) based upon high LD (r 2 = 0.98).…”
Section: Methodssupporting
confidence: 75%
“…Glucokinase regulatory gene (GCKR) is located in chromosome 2p23, expressed in liver tissue, and its protein inhibits glucokinase in hepatocytes [ 217 ]. Rs780094 (T>C) and rs1260326 (T>C/T>G) are two variants that have been identified to be associated with increased risk of NAFLD in various genetic models, with the former variant being more common [ 218 , 219 ]. A proposed mechanism by which rs780094 may predispose to NAFLD is that the variant protein does not exert inhibitory effect on glucokinase, therefore, there is an activation of de novo lipogenesis, TG and cholesterol synthesis [ 220 ].…”
Section: Omics-related Diagnostic Research Technologiesmentioning
confidence: 99%
“…And diabetes and fatty liver are often associated 45 . Some studies have identified that GCKR rs1260326 and GCKR rs780094 were significantly associated with MAFLD 11,46 . However, there was no correlation between the GCKR variants and the risk of MAFLD in the study.…”
Section: Discussionmentioning
confidence: 57%
“… 45 Some studies have identified that GCKR rs1260326 and GCKR rs780094 were significantly associated with MAFLD. 11 , 46 However, there was no correlation between the GCKR variants and the risk of MAFLD in the study. On the other hand, GCKR rs1260326 and GCKR rs780094 were associated with increased TG levels and reduced serum fasting glucose, which was also found in some studies.…”
Section: Discussionmentioning
confidence: 59%